2001
DOI: 10.1089/08942680152484108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Scatter and Attenuation on Aerosol Deposition as Determined by Gamma Scintigraphy

Abstract: Gamma scintigraphy is often used to quantify deposition patterns from aerosol inhalers. The errors caused by scatter and tissue attenuation in planar Tc-99m gamma scintigraphy were investigated based on the data collected from four subjects in this study. Several error correction methods were tested. The results from two scatter correction methods, Jaszczak's method and factor analysis of dynamic sequences (FADS), were similar. Scatter accounted for 20% of raw data in the whole lung, 20% in the oropharynx, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Borgstrom [72] found that planar imaging overestimated by 27% the amount of lung deposition of drug from a dry powder inhaler. This is precisely the predicted effect due to over-emphasis of peripheral deposition at the expense of central airway deposition [64] [61,62,69]. The same effect was most likely the cause of observed variability in deposition by Newman [4] , who observed anomalously high lung penetration of large particles in a study of the effect of particle size on distribution.…”
Section: Planar Imaging Problems and Pitfallssupporting
confidence: 57%
See 3 more Smart Citations
“…Borgstrom [72] found that planar imaging overestimated by 27% the amount of lung deposition of drug from a dry powder inhaler. This is precisely the predicted effect due to over-emphasis of peripheral deposition at the expense of central airway deposition [64] [61,62,69]. The same effect was most likely the cause of observed variability in deposition by Newman [4] , who observed anomalously high lung penetration of large particles in a study of the effect of particle size on distribution.…”
Section: Planar Imaging Problems and Pitfallssupporting
confidence: 57%
“…For example, the absorption rates of Tc-99m pertechnetate used in a common fashion as a tracer for triamcinolone acetonide drug particles in the human lung were measured, and then the absorption of [ 11 C]triamcinolone acetonide was determined using the same drug preparation in the same human volunteers. The absorption rate constant of Tc was approximately 0.07 min -1 , while that of triamcinolone acetonide was 0.03 min -1 [60][61][62].…”
Section: Planar Imaging Problems and Pitfallsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of planar imaging to measure total deposition in the lung has come under particular scrutiny in the literature. (16,17) It was therefore felt important to include a clear validation of the planar analysis of this study. This was done in two ways: (1) using the dose accountability experiment in which the total activity leaving the nebulizer measured using an isotope calibrator was compared to that obtained from gamma camera imaging, and (2) by comparing total lung activity measurements from planar imaging with those from SPECT.…”
Section: Discussionmentioning
confidence: 99%